Analysis on the risk of contralateral proximal femoral epiphyseal slippage using the modified Oxford score() - Soni, Jamil Faissal (Rev Bras Ortop, 2015)
OBJECTIVE: To determine the application of the modified Oxford score among patients with proximal femoral epiphyseal slippage (PFES) as an aid to indicating prophylactic surgical treatment on the contralateral hip. METHODS: Retrospective analysis on the medical files of patients attended at the institution where the authors work. From these, patients attended between 2008 and 2011 who presented unilateral PFES and were followed up for a minimum of two years were selected. Patients were excluded if they presented endocrine disease, metabolic disease, Down syndrome or radiographs that were inadequate for determining the modified Oxford score. The initial radiographs received scores ranging from 16 to 26. Statistical analysis was used to determine whether the scoring was predictive of future development of contralateral slippage. RESULTS: Among the 15 patients with unilateral PFES that were selected, five (33.3%) evolved with contralateral slippage. The patients were divided into two groups. Four patients were considered to present risk and three of them developed contralateral slippage. In the group that was considered not to present risk, there were 11 patients and two of these evolved with contralateral slippage. Thus, there was a tendency for the patients in the group that developed the disease to differ from the group that did not develop it, in relation to the risk classification. CONCLUSION: Although application of the modified Oxford score was not statistically significant in our sample, we noted a tendency toward contralateral slippage among hips with low scores.